Alum-Cs2CO3 as a New Recyclable Solid Base Catalyst for the Efficient Syntheses of Arylidenemalononitriles, Esters and Arylcinnamic Acids in Water - Kumar Taduri, Ashok; Rama Devi, B. (Asian Journal of Chemistry, 2014)
The condensation between aromatic aldehydes and malononitrile, ethylcyanoacetate and malonic acid for the syntheses of arylidenemalononitriles, arylidenemalonic acid esters and aryl cinnamic acids in water using alum-Cs2CO3 as a solid support catalyst has been described. Alum-Cs2CO3 was found to be a highly active, stable and recyclable catalyst under reaction conditions.